2016
DOI: 10.1085/jgp.201511538
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin kinase and arrestin binding control the decay of photoactivated rhodopsin and dark adaptation of mouse rods

Abstract: G-protein receptor kinase and arrestin 1 are required for inactivation of photoactivated vertebrate rhodopsin. Frederiksen et al. show that they additionally regulate the subsequent decay of inactive rhodopsin into opsin and all-trans retinal and therefore dark adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…), where corresponding kinetic rates are strongly associated in vivo with the recovery rate of dark adaptation (Frederiksen et al. ), as well as overall rod photosensitivity (Imai et al. ; Yue et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…), where corresponding kinetic rates are strongly associated in vivo with the recovery rate of dark adaptation (Frederiksen et al. ), as well as overall rod photosensitivity (Imai et al. ; Yue et al.…”
Section: Discussionmentioning
confidence: 99%
“…Visual performance in organisms is reliant not only on wavelength detection, but also on the neural signaling of rod photoreceptors, which is initiated by rhodopsin-mediated phototransduction. This proceeds through a complex series of inactive-and active-state rhodopsin conformations that exist in temperature-and pH-dependent photochemical equilibria (Schafer et al 2016;Van Eps et al 2017), where corresponding kinetic rates are strongly associated in vivo with the recovery rate of dark adaptation (Frederiksen et al 2016), as well as overall rod photosensitivity (Imai et al 2007;Yue et al 2017). In particular, the spontaneous thermal decay rate of the inactive dark-state conformation and the decay rate of the light-activated MII conformation are two distinct nonspectral functional properties considered evolutionary innovations to dim light (Aho et al 1988;Imai et al 1997;Lamb et al 2016;Yue et al 2017).…”
Section: Rhodopsin Kinetics At High Altitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dark adaptation is typically defined as the ability to regain photosensitivity after bright light stimulation, which, in the case of rods, is very slow, requiring 1‐3 hours . In both rods and cones, dark adaptation requires regeneration of the bleached visual pigment, a process that involves the dephosphorylation of the opsins, the release of all ‐trans ‐retinal from the pigment, and the binding of fresh 11‐ cis ‐retinal following its recycling . Recently, it has been shown that both rhodopsin and the M‐cone pigment are dephosphorylated by protein phosphatase 2A (PP2A), allowing them to reset to their ground state in a timely fashion and respond to another photon …”
Section: Introductionmentioning
confidence: 99%